1987
DOI: 10.1109/edl.1987.26601
|View full text |Cite
|
Sign up to set email alerts
|

Thin polyoxide films grown by rapid thermal processing

Abstract: The growth of thin (80-200 A ) oxide films by rapid thermal processing (RTP) on LPCVD poly and amorphous silicon is reported. Oxide growth kinetics are affected by dopant concentration, implant species, and preoxidation anneal conditions. Breakdown fields > 11 MV/ cm have been measured. Constant current stress measurements indicate a higher rate of negative charge trapping in oxides grown on top of polysilicon as compared to amorphous silicon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Therefore, RTOi is expected to improve the dielectric strength. Similar results have been reported for RTO1 polyoxides grown on amorphous Si, in situ phosphorus doped or arsenic implantation doped poly-Si (11,12). Electron trapping properties.-- Figure 3 plots the changes of the applied field (AEox) under an electron injection of 100 p2gcm 2 as a function of stress time for both bias polarities.…”
Section: Comparison Of Rapid Thermal Oxidation and Furnacesupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, RTOi is expected to improve the dielectric strength. Similar results have been reported for RTO1 polyoxides grown on amorphous Si, in situ phosphorus doped or arsenic implantation doped poly-Si (11,12). Electron trapping properties.-- Figure 3 plots the changes of the applied field (AEox) under an electron injection of 100 p2gcm 2 as a function of stress time for both bias polarities.…”
Section: Comparison Of Rapid Thermal Oxidation and Furnacesupporting
confidence: 74%
“…RTO1 of poly-Si results in an increase of ~B,efr for both bias polarities due to the relatively smooth poly-Si/polyoxide interfaces (11,12). After nitridation, the calculated %,eft for both + Vg and -Vg decreases with RTN directly due to the incorporated nitrogen at both poly-Si/polyoxide interfaces.…”
Section: Effects Of Rapid Thermal Reoxidationmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, the difference in refractive index may result from surface roughness created during the doping, annealing, and oxidation of poly (10,19,20). It has been shown that roughness at the Si-SiO2 interface can be modeled as an additional film at the interface with composite refractive index (21).…”
Section: Discussionmentioning
confidence: 99%